COVID-19 pandemic hazard–risk–vulnerability analysis: a framework for an effective Pan-India response. Issue 25 (13th December 2022) - Lal, Preet; Kumar, Amit; Prasad, Alisha; Kumar, Shubham; Saikia, Purabi; Dayanandan, Arun; Roy, Parth Sarathi; Khan, Mohammed Latif
Abstract: This study evaluated the COVID-19 risk considering positive cases (as a hazard) and the demographic structure (as a socio-economic vulnerability) at districts scale across India using fuzzy analytical hierarchical process and geospatial modelling. Despite the fact that the high and very high COVID-19 hazard was observed in a limited area (14.2%, 233 districts), the proportion of high to very high COVID-19 risk was evident in larger regions (42.5%, 575 districts). A moderate to very high socio-economic vulnerability was recorded in major parts of the country (60.0%, 557 districts), while the districts with megacities had been severely affected due to the more complex urban and social systems. The study highlights the zones under high COVID-19 hazard and its possible linkages with vulnerability and risk at district scales in India that may effectively support emergency preparedness and response mechanisms during the different waves of the pandemic.